METHODOLOGICAL REFLECTION ON THE HETEROCHRONIA IN THE CONTEXT OF DEVELOPMENT OF A HEALTH PRESERVING COMPETENCE OF A PHYSICAL EDUCATION TEACHER - Yevtuch, Mykola; Fedorets, Vasyl; Klochko, Oksana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article presents the methodology of using knowledge about the phenomenon of heterochronia in pedagogy. The aim of the study is to improve the methodology of development of health-saving competence of Physical Education teacher in postgraduate education based on actualization and understanding of the phenomenon of heterochronia. The use of knowledge about the phenomenon of heterochronia is considered in the context of pedagogical anthropology and conducted within the framework of phenomenological, health-saving and anthropological approaches. Approaches used in the research are the following: competence, axiological, existential, transdisciplinary, etc. Due to the use of the phenomenon of heterochronia, the temporal phenomenology of a person is represented, as well as its non-linearity, processability. Knowledge of the phenomenon of heterochronia and its value interpretations is used in the pedagogical methodology of prevention of sudden cardiac death. The use of knowledge of heterochronia promotes the effective application of Physical Education teacher the knowledge of human morphophysiology in educational practices of health preservation and axiologicalization and humanization of the educational process. The results of the conducted study determine quite considerable prevalence of knowledge as well as value and health oriented understandings of heterochronia among the working Physical Education teachers in comparison with students mastering this profession.